2005
DOI: 10.1007/s00411-005-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

The Hiroshima thermal-neutron discrepancy for 36Cl at large distances. Part I: New 36Cl measurements in granite samples exposed to A-bomb neutrons

Abstract: The long-lived radioisotope (36)Cl (half-life: 301,000 years) was measured in granite samples exposed to A-bomb neutrons at distances from 94 to 1,591 m from the hypocenter in Hiroshima, by means of accelerator mass spectrometry (AMS). Measured (36)Cl/Cl ratios decrease from 1.6 x 10(-10) close to the hypocenter to about 1-2 x 10(-13), at a distance of 1,300 m from the hypocenter. At this distance and beyond the measured (36)Cl/Cl ratios do not change significantly and scatter around values of 1-2 x 10(-13). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…The DS86 was replaced by the dosimetry system 2002 (DS02) 5) . For the distant samples, the newly calculated 36 Cl/Cl ratios were also approximately coincident with those measured in Munich 6,7) . The height of the epicenter in the DS02 was 600 m while that in the DS86 was 580 m. The replacement of the dosimetry system made the calculated 36 Cl/Cl ratios lower at close ranges, but they were still larger than measured ratios 6,7) .…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…The DS86 was replaced by the dosimetry system 2002 (DS02) 5) . For the distant samples, the newly calculated 36 Cl/Cl ratios were also approximately coincident with those measured in Munich 6,7) . The height of the epicenter in the DS02 was 600 m while that in the DS86 was 580 m. The replacement of the dosimetry system made the calculated 36 Cl/Cl ratios lower at close ranges, but they were still larger than measured ratios 6,7) .…”
Section: Introductionsupporting
confidence: 76%
“…For the distant samples, the newly calculated 36 Cl/Cl ratios were also approximately coincident with those measured in Munich 6,7) . The height of the epicenter in the DS02 was 600 m while that in the DS86 was 580 m. The replacement of the dosimetry system made the calculated 36 Cl/Cl ratios lower at close ranges, but they were still larger than measured ratios 6,7) . Komura et al 8) measured 152 Eu/Eu ratios in several granite samples from ground distances of 146-1411 m. Most of the ratios were in agreement with those calculated by the DS02.…”
Section: Introductionsupporting
confidence: 76%
“…Nevertheless, this problem in terms of the dosimetry for distant locations had been resolved within a few years from 2001. In the same year, 2001, Ruehm reported that the re-measurements of 36 Cl agreed with the preliminary results from new calculations for locations further than 1.2 km, which was later confirmed and published in 2005 [ 35 ]. The consistency in 36 Cl triggered the re-measurement of 152 Eu up to statistics of an order of magnitude.…”
Section: Introductionsupporting
confidence: 67%
“…In the second paper, Huber and co-workers determined the long-lived radioisotope 36 Cl in granite samples exposed to the A-bomb neutrons at various distances from the Hiroshima hypocenter. 205 It was found that very close to the hypocenter, the 36 Cl/Cl ratio was 1.6 Â 10 À10 , but that this decreased to approximately 2 Â 10 À13 further away (1200 m) and then stayed approximately constant. It was concluded that the 36 Cl had been produced by the neutron capture by stable 35 Cl.…”
Section: Nuclear Materialsmentioning
confidence: 94%